Treatment with PCSK9 inhibitors reduces atherogenic VLDL remnants in a real-world study - Hollstein, Tim; März, Winfried (Vascular pharmacology, 2019)
Background - Proprotein convertase subtilisin-kexin type 9 inhibitors (PCSK9-I) reduce low-density lipoprotein (LDL) cholesterol in human studies. Previous studies suggest that PCSK9-I may also affect very-low-density lipoproteins (VLDL). We therefore studied VLDL size and composition in a “real-world” study population with the use of β-quantification. - Subjects and methods - 350 patients (62±11years old, 58% men, 22% with diabetes mellitus) with different concomitant lipid lowering therapies, and in whom PCSK9-I treatment was indicated, received either evolocumab (140mg) or alirocumab (75 or 150mg). The major lipoprotein fractions were separated by β-quantification and lipid and apolipoprotein compositions were determined before and 4weeks after initiation of PCSK9-I treatment. - Results - After 4weeks of PCSK9-I treatment, the ratio of triglycerides to apolipoprotein B in VLDL particles (VLDL-TG/apoB ratio) increased by 40% (p<.0001). VLDL-associated apolipoproteins E, CII, and CIII were reduced by 29.4%, 16.4%, and 12.4%, respectively (all p<.0001). - Conclusion - PCSK9-I treatment increased VLDL size (estimated by an increased VLDL-TG/apoB ratio) and reduced VLDL-associated apolipoproteins in a heterogeneous “real-world” study-population, reflecting a higher clearance of small atherogenic VLDL remnant particles by PCSK9-I. This may potentially lower cardiovascular risk in clinical routine patients beyond low-density cholesterol (LDL-C) reduction.